EVERYDAY PRACTICES IN THE NEW MEDIA DISCOURSE (BY THE EXAMPLE OF COOKING SHOWS) / ПОВСЕДНЕВНЫЕ ПРАКТИКИ В ДИСКУРСЕ НОВЫХ МЕДИА (НА ПРИМЕРЕ КУЛИНАРНЫХ ШОУ) - SIYUKHOVA AMINET M. / СИЮХОВА А.М. (Наука телевидения, 2020)
The article addresses the everyday practices as the content of screen media programs. The main object of analysis is television programs devoted to food and cooking as the most popular ones in a series of programs about everyday practices. The purpose of the study is to identify factors that determine the constant production and particular popularity of cooking shows on television. The research methodology is based on a systematic approach that allows us to consider conscious cooking as a cultural-producing phenomenon from philosophical, sociological and cultural points of view. An important area of research is the identification of the aesthetic and artistic potential of representing food through art. The idea that food in the space of living nature is initially the main condition for its physical existence, while consciously prepared food is a cultural universal that fundamentally distinguishes humans from wild animals, is drawn as a philosophical thesis. A culturological approach to the study of the phenomenon of food consists in the ability of food to encode meanings of human life, which contributed to its introduction into the context of various symbolic practices, such as magic, religious rites, and art. The aesthetic apprehension of food is historically determined by the interest of the collective consciousness in the immanent essence of cooking as magic, based on its ability to recreate metamorphoses, i.e. transformation of a product into its opposite (hard to soft, liquid to thick, etc.). The sociological understanding of the meaning of food emphasizes the idea that cooperative procurement of food, the removal of “strangers” from its reserves, the formation of certain taboos during the distribution of food, etc., have organized a social structure. The semantics of the “eternal struggle for daily bread” is realized in cooking shows associated with fierce competition. The main conclusion of the study is that cookery, as a form of everyday practices of our time in the context of media art, can carry multidirectional semantic charges and fulfill missions determined by the values of the content authors—from humanistic ideas to harmonize our existence in nature and society, to ideas of society massification with an imperative motivation of individuals for excessive symbolic consumption of goods and services.